Protective effects of morin against acrylamide-induced hepatotoxicity and nephrotoxicity: A multi-biomarker approach. (April 2020) - Kandemir, Fatih Mehmet; Yıldırım, Serkan; Kucukler, Sefa; Caglayan, Cuneyt; Darendelioğlu, Ekrem; Dortbudak, Muhammet Bahaeddin
Abstract: Acrylamide (ACR) is a heat-induced carcinogen substance that is found in some foods due to cooking or other thermal processes. The aim of present study was to assess the probable protective effects of morin against ACR-induced hepatorenal toxicity in rats. The rats were treated with ACR (38.27 mg/kg b.w., p.o.) alone or with morin (50 and 100 mg/kg b.w., p.o.) for 10 consecutive days. Morin treatment attenuated the ACR-induced liver and kidney tissue injury by diminishing the serum AST, ALP, ALT, urea and creatinine levels. Morin increased activities of SOD, CAT and GPx and levels of GSH, and suppressed lipid peroxidation in ACR induced tissues. Histopathological changes and immunohistochemical expressions of p53, EGFR, nephrin and AQP2 in the ACR-induced liver and kidney tissues were decreased after administration of morin. In addition, morin reversed the changes in levels of apoptotic, autophagic and inflammatory parameters such as caspase-3, bax, bcl-2, cytochrome c, beclin-1, LC3A, LC3B, p38α MAPK, NF-κB, IL-1β, IL-6, TNF-α and COX-2 in the ACR-induced toxicity. Morin also affected the protein levels by regulating the PI3K/Akt/mTOR signaling pathway and thus alleviated ACR-induced apoptosis and autophagy. Overall, these findings may shed some lights on new approaches for the treatment of ACR-induced hepatotoxicity and nephrotoxicity. Graphical abstract: Image 1 Highlights: Morin protects rats against ACR-induced hepatotoxicity and nephrotoxicity. Morin reduces apoptosis and autophagy in the ACR-induced toxicity. Morin depressed levels of oxidative stress and pro-inflammatory cytokines. Morin regulated the PI3K/Akt/mTOR signaling pathway in the ACR-induced toxicity.